Babylonian Astronomy. III. The Earliest Astronomical Computations - Van der Waerden, B. L.
1. Summary — 2. The Older System — 3. The Circular Astrolabe — 4. The 14th Tablet of the Great Omen Series — 5. The Meaning of igi.du8-a = tâmartu — 6. The Later System — 7. The Ivory Prism — 8. Popular and Astronomical Units of Time — 9. The Visibility of the Moon according to Roman Sources — 10. How to Tell the Time during the Night from Rising Zodical Signs — 11. Later Computations of the Rising and Setting of the Moon — 12. Later Computations of Daylight and Night — 13. Other Applications of Arithmetical Series — 14. Arithmetical Series in Greek Astronomy — 15. The Shadow Length.